G+2(3+g)=4(g+1)

Simple and best practice solution for G+2(3+g)=4(g+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for G+2(3+g)=4(g+1) equation:


Simplifying
G + 2(3 + g) = 4(g + 1)
G + (3 * 2 + g * 2) = 4(g + 1)
G + (6 + 2g) = 4(g + 1)

Reorder the terms:
6 + G + 2g = 4(g + 1)

Reorder the terms:
6 + G + 2g = 4(1 + g)
6 + G + 2g = (1 * 4 + g * 4)
6 + G + 2g = (4 + 4g)

Solving
6 + G + 2g = 4 + 4g

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + G + -6 + 2g = 4 + -6 + 4g

Reorder the terms:
6 + -6 + G + 2g = 4 + -6 + 4g

Combine like terms: 6 + -6 = 0
0 + G + 2g = 4 + -6 + 4g
G + 2g = 4 + -6 + 4g

Combine like terms: 4 + -6 = -2
G + 2g = -2 + 4g

Add '-2g' to each side of the equation.
G + 2g + -2g = -2 + 4g + -2g

Combine like terms: 2g + -2g = 0
G + 0 = -2 + 4g + -2g
G = -2 + 4g + -2g

Combine like terms: 4g + -2g = 2g
G = -2 + 2g

Simplifying
G = -2 + 2g

See similar equations:

| 2=400/x | | (x+5y)dy=-(2x+3y)dx | | 7=5(x+5)-7x | | onethird(x+3)+onesixth(x-6)=x+3 | | 5xa-7a^2=2a^2+2ax | | -6x-3(7x-26)=-111 | | 4a-2a+11=6a-13 | | 9w+5= | | 5ax-7a^2=2a^2+2ax | | 8(-7+8v)=200 | | 9w-5= | | 1p-15=13-6p | | 10p+6=-18-2p | | 29=4x-5 | | 2x^2=-2 | | -9v-6+7v=16 | | (2x+1500)-(4x-1800)=0 | | 5x-13=11+3x | | -18-[3(x+2)+4]=21-[6(-2x-2)+1] | | (x+5y)dy+(2x+3y)dx=0 | | -(5/12)y=25 | | 16+3s-2s=24+2s | | xxxx=69 | | 3x^2+36x+96= | | x.x.x.x=69 | | 5x-6(2x)=14 | | -5m+2+8m=2m | | -84-17x=-169 | | -2.3q+16=-5q+-38 | | 3(w+1)=5w-1 | | 47x+149=133 | | 3w+6=-w+30 |

Equations solver categories